BOOK REVIEW: SUSTAINABLE LIVELIHOODS AND RURAL DEVELOPMENT - Ariyanto, Komang (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
The book is 168 pages thick with content full of knowledge (theoretical and practical) through various interrelated concepts in building a better livelihood framework. This book is very worth reading. This reminds that it can be understood and can be used by institutions or individuals who want and are currently carrying out development work in poverty alleviation, as well as in development studies and multidimensional rural development. This book can be read, both theoretically and practically, to encourage rural development planners and local institutions to reflect again on policies that are pro-poor, pay attention to local parameters, and voice the aspirations of the community and local institutions at a more macro level. Finally, this book gives us an understanding of the study of rural development, especially poverty alleviation through the subject's livelihood. Moreover, in elaborating Henry Bernstein's political-economy approach which can be applied from the smallest unit, such as the household to a wider spectrum, to the global realm so that it can enrich and strengthen the analysis of sustainable livelihoods at various loci. However, this book also needs to add related issues related to connectivity and discussion with the global development agenda SGDs, and needs case studies on sustainable livelihoods globally as reference material and strengthens the political economy perspective that has been described in the case study.